Epigenetics as a key link between psychosocial stress and aging: concepts, evidence, mechanisms . Issue 4 (31st December 2019) - Zannas, Anthony S.
Abstract : Psychosocial stress—especially when chronic, excessive, or occurring early in life—has been associated with accelerated aging and increased disease risk. With rapid aging of the world population, the need to elucidate the underlying mechanisms is pressing, now more so than ever. Among molecular mechanisms linking stress and aging, the present article reviews evidence on the role of epigenetics, biochemical processes that can be set into motion by stressors and in turn influence genomic function and complex phenotypes, including aging-related outcomes. The article further provides a conceptual mechanistic framework on how stress may drive epigenetic changes at susceptible genomic sites, thereby exerting systems-level effects on the aging epigenome while also regulating the expression of molecules implicated in aging-related processes. This emerging evidence, together with work examining related biological processes, begins to shed light on the epigenetic and, more broadly, molecular underpinnings of the long-hypothesized connection between stress and aging.